Teacher’s Speaking Strategies at Vocational High School - Syafrizal Syafrizal; Cucum Rohmawati (English Department - University of Sultan Ageng Tirtayasa, 2017)
The aim of Study is portraying teacher’s strategies in teaching speaking to students at vocational high school level and recognizing students’ response towards the strategies by involving an English teacher and a class of 38 students. In collecting the data, classroom observation and interview were conducted to identify the strategies of teaching speaking, and questionnaire was administered to the students to gain the data about their response towards the strategies under the umbrella of descriptive research. The result revealed that the strategies used by the teacher were cooperative activities, role-play, creative tasks, and drilling. In the meantime, students’ response towards the strategies resulted in positive attitude as they responded that the strategies helped them to speak, as well as concerned oral production of students whose participation was emphasized. Key words: Teaching strategies, the teaching of speaking, vocational high school students